2022
DOI: 10.3390/su142013562
|View full text |Cite
|
Sign up to set email alerts
|

Multi-State Car-Following Behavior Simulation in a Mixed Traffic Flow for ICVs and MDVs

Abstract: With the development of intelligent connected vehicles (ICVs) and communication technology, collaborative operation among vehicles will become the trend of the future. Thus, traffic flow will be mixed with manual driving vehicles and ICVs. A mixed traffic flow is a traffic flow state lying between autonomous and manual traffic flows. In order to describe the car-following characteristics in a mixed traffic flow, the cooperative adaptive cruise control (CACC) car-following model and the intelligent driver model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…The input of the model is the speed of the car in front, the distance between the car and the car in front and the speed of the car. The output is the acceleration of the car [34]. The IDM is suitable to be applied to the research of this paper, and it is expressed as follows:…”
Section: Guidance Model Of Cavsmentioning
confidence: 99%
See 2 more Smart Citations
“…The input of the model is the speed of the car in front, the distance between the car and the car in front and the speed of the car. The output is the acceleration of the car [34]. The IDM is suitable to be applied to the research of this paper, and it is expressed as follows:…”
Section: Guidance Model Of Cavsmentioning
confidence: 99%
“…The channelization diagram of the Jinjiling-Jiefang intersection is shown in Figure 4, the phase scheme of the signal control is shown in Table 1 and the traffic volume and the number of lanes at the intersection are shown in Table 2. The parameters of the CAV simulation set in this study refer to those from existing studies [33,34], and the main parameters of the simulation calculation are shown in Table 3.…”
Section: Numerical Casementioning
confidence: 99%
See 1 more Smart Citation
“…Chen Jie et al [3] found that the following stability of traffic flow is affected by the values of the number of communicating vehicles and sensitivity of the networked vehicles, and the higher the penetration rate of the networked vehicles, the greater the improvement of the accessibility. Song Chengju et al [4] analyzed the following characteristics of different car-following models and carried out simulation studies using the CACC model for the stationary and perturbed states of the following queue, and the results showed that, in the case of a higher penetration rate of CAVs, the speed of traffic flow is negatively correlated with the volume of traffic and with the increase in penetration rate, the traffic volume in general is on the rise. Hou Peiguo et al [5] based on the Nasch cellular automata traffic flow model, considering the psychological factors of traditional drivers and driving behavior differences, to establish a manual driving-CACC automatic driving mixed traffic flow model, and concluded that with the increase in the proportion of automatic driving vehicles, traffic flow volume, average speed increases, and other conclusions.…”
Section: Introductionmentioning
confidence: 99%